Punaga Beach Tourism Development Policy Strategy in Takalar District - Eka Wardana; Haedar Akib; Didin Didin (Jurnal Aktor, 2021)
Tourism is one of the comparative advantages that must be developed by each region. Takalar Regency is an area with a variety of tourism potentials, one of which is marine tourism. The Punaga beach tourism object in Takalar Regency is one of the tourism potentials in Takalar Regency that needs to be developed because it has the potential for stunning natural beauty but is inversely proportional to the number of tourist visits which are still very minimal, therefore an appropriate strategy is needed to support efforts to develop Punaga beach tourism objects. . This study uses a qualitative descriptive method by collecting data through observation, interviews, and documentation related to the research topic, then the data is processed using SWOT analysis to obtain a strategy for developing the Punaga beach tourism object. From the research results, several priority strategies can be formulated that can be used in efforts to develop Punaga beach tourism objects.